Patterns of connectivity in marine microbial communities - Marín, Carolina (2023)
Marín Vindas, C.(2023). Patterns of connectivity in marine microbial communities. [Tesis de Doctorado]. Universitat Politècnica de Catalunya, Departament de Biologia Marina i Oceanografia, Institut de Ciènciesdel Mar, CSIC; España.